Interlaboratory variation in the performance of liquid‐based cytology: Insights from the ATHENA trial. Issue 8 (29th October 2013) - Wright, Thomas C.; Stoler, Mark H.; Behrens, Catherine M.; Sharma, Abha; Sharma, Keerti; Apple, Raymond
<x xml:space="preserve">Abstract</x> Although it is recognized that cervical cytology is highly subjective, and that there is considerable interlaboratory variation in how slides are evaluated, little is known as to how this impacts the performance of cytology. In the ATHENA trial, liquid‐based cytology specimens from 46, 887 eligible women ≥21 years of age were evaluated at four large regional US laboratories, providing a unique opportunity to evaluate the impact of interlaboratory variations on the performance of cervical cytology. All women with abnormal cytology (atypical squamous cells of undetermined significance or higher) were referred to colposcopy, as were all high‐risk human papillomavirus (hrHPV)–positive women ≥25 years of age and a random subset of those ≥25 years of age who were negative by both hrHPV testing and cytology. Sociodemographics, risk factors for cervical disease, and prevalence of cervical intraepithelial neoplasia (CIN) were similar across the laboratories. There were considerable differences among the laboratories both in overall cytological abnormal rates, ranging from 3.8 to 9.9%, and in sensitivity of cytology to detect CIN grade 2 or worse (CIN2+), from 42.0 to 73.0%. In contrast, the hrHPV positivity rate varied only from 10.9 to 13.4%, and the sensitivity of hrHPV testing from 88.2 to 90.1%. These observations suggest that hrHPV testing without cytology should be considered as the initial method for cervical cancer screening.